1997
DOI: 10.1111/j.1348-0421.1997.tb01950.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Human Oral Spirochetes by Collagen‐Binding Proteins

Abstract: The ability of spirochetes to adhere to collagens was compared among three species of human oral treponemes. Immunoblot analysis demonstrated that type I-, IV-, and V-collagen-binding polypeptides (CBPs) were detected in the heated and unheated preparations from both Treponema denticola ATCC 33520 and T socranskii subsp. buccale ATCC 35534. Few CBPs, however, were detected in the heated and unheated preparations from a recently characterized isolate, T medium strain G7201. Immunoelectron microscopy using rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
0
23
2
Order By: Relevance
“…These include the virulence factors CNE of Streptococcus equi (29) and Acm of Enterococcus faecium (35), the surface proteins RspA and RspB of Erysipelothrix rhusiopathiae (46), the S-layer protein CbsA of the nonpathogenic bacterium Lactobacillus crispatus (32,49), and the adhesin YadA found in Yersinia enterocolitica and Yersinia pseudotuberculosis (53). Treponema also has the ability to bind collagen directly by collagen-binding polypeptides (54,55).In contrast to the above, previous studies using isolated collagen have been unable to detect a direct interaction between this ECM component and whole B. burgdorferi cells (4,(20)(21)(22). This is despite the fact that B. burgdorferi is mainly an extracellular pathogen that migrates actively from the dermis into the bloodstream and from the blood into connective tissues of organs, such as the heart.…”
contrasting
confidence: 38%
“…These include the virulence factors CNE of Streptococcus equi (29) and Acm of Enterococcus faecium (35), the surface proteins RspA and RspB of Erysipelothrix rhusiopathiae (46), the S-layer protein CbsA of the nonpathogenic bacterium Lactobacillus crispatus (32,49), and the adhesin YadA found in Yersinia enterocolitica and Yersinia pseudotuberculosis (53). Treponema also has the ability to bind collagen directly by collagen-binding polypeptides (54,55).In contrast to the above, previous studies using isolated collagen have been unable to detect a direct interaction between this ECM component and whole B. burgdorferi cells (4,(20)(21)(22). This is despite the fact that B. burgdorferi is mainly an extracellular pathogen that migrates actively from the dermis into the bloodstream and from the blood into connective tissues of organs, such as the heart.…”
contrasting
confidence: 38%
“…The washed membranes were incubated with 1% skim milk-TBS as blocking solution for 1 hr. The rabbit albumin-binding polypeptides from the treponemal cells were examined by incubation of the treponemal polypeptide-loaded nitrocellulose membranes with PBS, or rabbit albumin solution (120-360 ug/ml), for 2 hr at 4 C, followed by washing with Tween 20-TBS, blocking with skim milk-TBS, and incubation with the horseradish peroxidase (HRP)-conjugated sheep anti-rabbit albumin serum (I: 1,000 dilution; Bethyl Laboratories Inc., Montgomery, Tex., U.S.A.) for 2 hr at room temperature, as described by Umemoto et al (25).…”
Section: Methodsmentioning
confidence: 99%
“…Location of the rabbit albumin-binding polypeptides on the treponemal cells was carried out by immunoelectron microscopy as described by Umemoto et al (25). Briefly, the T. denticola and T. vincentii cells of each 4-day culture were gently washed twice with 0.01 M phosphate-buffered saline (PBS, pH 7.2), fixed for 1 hr at room temperature in 4% paraformaldehyde-0.5% glutaraldehyde fixate (pH 7.0), and washed twice with 1% glycine-PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Fenno et al (17) also found that recombinant Msp did not show an oligomeric form but it adhered to fibronectin and laminin. Umemoto et al (84,86) reported that T vincentii and T socranskii subsp. huecale have outer envelope proteins that bind to laminin, and that the 95 kDa outer sheath protein of T medium binds to type IV collagen.…”
Section: Adherencementioning
confidence: 99%